2014
DOI: 10.1080/00927872.2013.766796
|View full text |Cite
|
Sign up to set email alerts
|

Drinfeld Double for Braided Infinitesimal Hopf Algebras

Abstract: In this paper, we mainly construct the Drinfeld double for braided infinitesimal Hopf algebras in Yetter-Drinfeld categories as a generalization of Aguiar's result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Moreover, the notions of coboundary and quasitriangular infinitesimal bialgebra, infinitesimal Hopf algebra, and the basic theory were established by Aguiar in [1,2]. Further research can be found in [4,27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the notions of coboundary and quasitriangular infinitesimal bialgebra, infinitesimal Hopf algebra, and the basic theory were established by Aguiar in [1,2]. Further research can be found in [4,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, infinitesimal bialgebras are also closely related to associative Yang-Baxter equations, Drinfeld's doubles, pre-Lie algebras and Drinfeld's Lie bialgebras [2]. Recently, Wang [39] generalized Aguiar's results by studying the Drinfeld's double for braided infinitesimal Hopf algebras in Yetter-Drinfeld categories. Another different version of infinitesimal bialgebras and infinitesimal Hopf algebras was defined by Loday and Ronco [35] and further studied by Foissy [15,16], in the sense that (2) ∆(ab) = a · ∆(b) + ∆(a) · b − a ⊗ b for a, b ∈ A.…”
Section: Introductionmentioning
confidence: 99%
“…The basic theory of infinitesimal bialgebras and infinitesimal Hopf algebras was developed by Aguiar [1,3,4,5], has proven useful not only in combinatorices [4,18], but in other areas of mathematics as well, such as associative Yang-Baxter equations [1,5], Drinfeld's doubles [1,39] and pre-Lie algebras [1]. The second version of infinitesimal bialgebras was defined by Loday and Ronco [31] and brought new life on rooted trees by Foissy [21,22] in the sense that…”
Section: Introductionmentioning
confidence: 99%